if u=XY+yz+zx,X=1/t,y=e^tz=e^-t find du/dt
Answers
If u = xy + yz + zx, where x=1/t, y=e^t, z=e^-t, then
du/dt = (1/t) (e^t - e^(-t)) - (1/t^2)(e^t + e^-t)
Given:
u = xy + yz + zx, where x=1/t, y=e^t, z=e^-t
To find:
du/dt
Solution:
u = xy + yz + zx
=> du/dt = d(xy + yz + zx)/dt
=> du/dt = d(xy)/dt + d(yz)/dt + d(zx)/dt
(Using uv rule, d(uv)/dx = u d(v)/dx + v d(u)/dx)
=> du/dt = x d(y)/dt + y d(x)/dt + y d(z)/dt + z d(y)/dt + z d(x)/dt + x d(z)/dt
Substituting the values of x, y and z in this expression, we get
=> du/dt = (1/t) d(e^t)/dt + e^t d(1/t)/dt + e^t d(e^-t)/dt + e^-t d(e^t)/dt + e^-t d(1/t)/dt + (1/t) d(e^-t)/dt
(We know
d(1/x)/dx = -1/x^2; d(e^x)/dx = e^x)
=> du/dt = (1/t) e^t + e^t (-1/t^2) + e^t (-e^-t) + e^-t e^t + e^-t (-1/t^2) + (1/t)(-e^-t)
=> du/dt = (1/t) e^t + e^t (-1/t^2) - 1 + 1 + e^-t (-1/t^2) + (1/t)(-e^-t)
=> du/dt = (1/t) (e^t - e^(-t)) - (1/t^2)(e^t + e^-t)
Hence,
du/dt = (1/t) (e^t - e^(-t)) - (1/t^2)(e^t + e^-t)
#SPJ1